Early-blocked asporogenous mutants of Bacillus subtilis are lysogenized at reduced frequency by temperate bacteriophages. - Ikeuchi, T (1978)
The establishment of lysogeny in early-blocked asporogenous (Spo-) mutants of Bacillus subtilis 168, which were also defective in the production of antibiotics (Abs-), by temperate phage phi105 or SPO2 was studied. It was found that the frequency of lysogenization of Spo-Abs-mutants was 10 to 20% that of the wild-type bacteria. There was no difference in the efficiency of plating and the burst size of phi105 between wild-type and mutant strains. Phi105 lysogens of mutant strains were as stable as those of the wild type. Several rifampin-resistant mutants defective in the production of antibiotics were isolated. They were also defective in spore formation and lysogenized by phi105 at reduced frequency.